Birdwatching Tourism Prospects for Papuan People In order to improve the standard of living of the community Malagufuk Village, Makbon District, Sorong Regency - Yerrynaldo Loppies; Amatus Turot; Jordan Tiblola (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Malagufuk Village is one of the most famous bird watching areas throughout the world. This is due to the various types of endemic Papuan birds that inhabit the area. Since its founding in 2014, this village has been visited by thousands of visitors. The problem for Papuans is that birdwatching tourism is not yet familiar to the local community, their knowledge of English and types of birds is low, and they do not understand the management of facilities that can support birdwatching tourism activities. The weak ability to utilize this potential affects the partner's standard of living. The current birdwatching market is foreign tourists who are fluent in Indonesian. To increase people's income through birdwatching tourism, it is necessary to conduct outreach and tourism management training. The specific target is to provide socialization and basic English training to provide the best service to bird watchers. With this community service activity, the people of Malagufuk Tourism Village have increased their ability and capacity to develop and utilize the potential that exists in tourism activities.